2013
DOI: 10.1590/s1413-81232013001100028
|View full text |Cite
|
Sign up to set email alerts
|

Pressão arterial elevada em adolescentes: prevalência e fatores associados

Abstract: Objetivou-se verificar a prevalência e os fatores associados à pressão arterial (PA) elevada em adolescentes de um município Brasileiro. Estudo transversal, conduzido em 653 adolescentes (57,9% do sexo feminino) de 14 a 19 anos de idade, estudantes do ensino médio. A Pressão arterial sistólica (PAS) e a diastólica (PAD) foram mensuradas em todos os sujeitos. Variáveis sociodemográficas, do estilo de vida e índice de massa corporal foram obtidas. Regressão logística binária, bruta e ajustada, foi empregada com … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
10
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 22 publications
5
10
0
4
Order By: Relevance
“…When the total sample was analyzed the results of this study corroborated previous studies that showed no association between physical activity and HBP in young people 9,11,[21][22][23] . The present study examined the practice of sports because the physical activity of young people is largely performed through sports 15 .…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…When the total sample was analyzed the results of this study corroborated previous studies that showed no association between physical activity and HBP in young people 9,11,[21][22][23] . The present study examined the practice of sports because the physical activity of young people is largely performed through sports 15 .…”
Section: Discussionsupporting
confidence: 86%
“…With regard to the participants who practiced sports, the prevalence of HBP was similar in young people who were overweight and obese compared to the eutrophic participants (17.1 and 18.2 vs 15.5%). In the adjusted analysis, young people who were overweight and obese in the total sample and those who did not practice sports showed a prevalence ratio of HBP which ranged from 1.60 to 2.15 higher than their eutrophic counterparts, results that corroborate those in previous studies [9][10][11]18,22,26 . No significant associations were found for young people who practice sports.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations